Effect of Preterm Infant Massage by the Mother on the Mood of Mothers Having Preterm Infants - Lotfalipour, Batool (J Chiropr Med, 2019)
OBJECTIVE: The purpose of this study was to determine the effect of preterm infant massage by the mother on the mood state of mothers of preterm infants. METHODS: This experimental study assessed 52 mothers of preterm infants (born at 30-37 weeks of gestation) hospitalized in the neonatal intensive care unit of Afzalipour Hospital of Kerman University of Medical Sciences, Iran. Recruitment was done using the convenience sampling method, and participants were randomly assigned into intervention and control groups. In the intervention group, massage therapy was done once a day for 5 consecutive days. Infants in the control group received the usual care. Data were collected using a questionnaire of demographic information and the Profile of Mood State questionnaire and analyzed using SPSS version 19 (IBM Corp, Armonk, New York) and Kruskal-Wallis, Mann-Whitney U, Wilcoxon, and χ(2) tests. RESULTS: Comparison of the mothers’ mean mood scores between the intervention and control groups showed no significant difference before the intervention (P = .51), whereas mean scores differed significantly after the intervention between the groups (P = .005). Mothers’ mean mood scores improved significantly in the control group (P = .02) and the intervention group (P < .001), whereas the intervention group showed a greater improvement (-4.155 vs -2.238). CONCLUSION: Those mothers performing massage on their preterm infants showed greater improvement in their mood compared with those in the control group. Teaching massage to the mothers of these infants could be considered as a possible intervention to enhance a mother’s mood and the quality of care she provides to her infant.